1975
DOI: 10.1901/jaba.1975.8-147
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Human Gastric Acid Secretion With Operant‐conditioning Procedures1

Abstract: In an attempt to control gastric acid secretion with operant-conditioning techniques, four normal women were given visual feedback on gastric pH plus money reinforcers.When money was made dependent on increased secretion in a differential-reinforcementof-high-rates schedule, the rate of secretion of three of the four subjects increased to three times baseline. When money was then made dependent on decreased secretion in a differential-reinforcement-of-other-behaviors schedule, the rate of secretion of these th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

1978
1978
2008
2008

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…The rate of gastric secretion can be reduced by visual biofeedback [86,87], It is unknown whether biofeedback is effective in NUD.…”
Section: Nonulcer Dyspepsiamentioning
confidence: 99%
“…The rate of gastric secretion can be reduced by visual biofeedback [86,87], It is unknown whether biofeedback is effective in NUD.…”
Section: Nonulcer Dyspepsiamentioning
confidence: 99%
“…Interestingly, this modality was first applied to treat neuromuscular disorders [7], Among the first applications in gastroen terology were attempts to achieve control over gastric acid secretion. These studies not only demonstrated the principles of biofeedback therapy, but also its problems and its limita tions [8][9][10][11], Studies were also performed to control gas tric motility but proved elusive [12][13][14], Oth er applications of biofeedback therapy were only marginally successful. Among them was the attempt to alter lower esophageal sphinc ter pressure in normal subjects and in patients with gastroesophageal reflux disease [15].…”
Section: Biofeedback In Gastroenterologymentioning
confidence: 99%
“…This is surprising in view of the fact that many of the earliest demonstrations of visceral discrimination (1) and control (2,3) dealt specifically with changes in the gastrointestinal system. Furthermore, several studies have indicated that operantconditioning techniques may be useful in the treatment of a variety of gastrointestinal disorders such as ruminative vomiting (4), fecal incontinence (5), and ulcers (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…One major problem is that it is difficult to ensure immediate feedback to the subject. Even when this problem is overcome, however (8), questions arise regarding both the psychological and the physiological impact of these invasive methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation